Menyentuh Hati dan Pikiran: Upaya Kontekstualisasi Katekese untuk Generasi Milenial dan Gen Z - Yohanes Hendro Pranyoto; Dedimus Berangka; Francisco Noerjanto (JURNAL PASTORAL KATEKETIK, 2024)
Millennials and Gen Z as the future of the Church have unique characteristics. These characteristics pose a challenge for traditional catechesis to reach and engage them in the proclamation of faith. This article explores the concept of contextualization of catechesis as a solution to overcome these challenges. Contextualization of catechesis can be defined as the process of adapting the message of faith to better suit the cultural and social audience. This contextualization of catechesis aims to make catechesis more relevant, interesting, and easily understood by the millennial generation and Gen Z. This article discusses catechesis contextualization strategies that can be applied, such as: understanding the characteristics and needs of millennials and Gen Z, utilizing technology and social media, involving millennials and Gen Z in the catechesis process, empowering creative and digitally literate catechists, and strengthening cooperation between family, Church, and school. In conclusion, contextualizing catechesis is an important and mandatory effort to reach and involve millennials and Gen Z so that they do not feel alienated in the Church. The author uses the term: “In through their door, out through our door”, because by applying the right strategy, contextualization of catechesis can touch the hearts and minds of millennials and Gen Z, helping them to grow in faith and Christian values.